Leveraging customer segmentation on hotel loyalty programs with data mining - Caetano, Joana Maria Pereira Lupi (2020)
This study aims to provide a new customer segmentation solution for hotels’ loyalty programs using a data mining approach forclassifying the customers into segments through clustering processes.Mainfindings suggest somehigh tier members are not as valuable as lower tier ones, there are groups of clients with distinct brand preferences, stay duration anddestination patterns which are not being correctly grouped due to tier segmentation andthatloyalty programs are not equally suitable for all brands within a hotel group, therefore additional levels of segmentation would be appropriate to match the distinct guests’behaviorand value.